Design with (human) nature: recovering the creative instrumentality of social data in urban design. Issue 2 (4th March 2019) - Kullmann, Karl
Abstract: In the mid-twentieth century, environmental psychology emerged as a field of significant potential that aimed to methodically decipher the influence of environments on human behaviour. However, by the 1980s innovation slowed, due in part to the limitations of the analogue technologies and techniques of the day that curtailed the field's wider application to urban design and planning. Across a similar timeframe, ecologically based methods for organizing the urban landscape also waned. However, unlike environmental psychology, ecological planning underwent considerable renewal in the late 1990s. Technology played a significant role, with access to ubiquitous high-resolution satellite imagery and advances in GIS applications ultimately catalyzing the urban design paradigm of landscape urbanism. Although useful, the ecological design framework that came to define landscape urbanism offered only a partial account of urban design. To address this imbalance, this paper considers how a technologically stimulated revitalization of the social side of urban design might mirror the renewal of ecological planning that occurred through digital satellite mapping. After canvassing the role of neuroscience and spatially aware devices in contemporary environmental psychology, the potential influence of drone mapping technology on urban design practice and theory is explored in depth.